Comparison of Chemical Properties and Application as Acid Soil Amendment of Pretreatment Center Slag and Other Slags - Suwarno Suwarno; Itsuo Goto; Hiroshi Masujima (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 1999)
Chemical properties of Pretreatment center slag (PTC-slag) were analyzed and compared to those of converter slag (C slag) and blast furnace slag (BF slag). PTC slag had a high EC value as well as citric acid soluble P and contained more Ca, Si, P, K, and Na but less Mg and Fe than C slag. Compared to BF slag, PTC slag contained more Fe, Ca, Mg, P, Mn, and Na but less Si, Al, and K. Although neutralizing value of PTC slag was lower than that of C slag, its ability to neutralize soil acidity was markedly higher. A pot experiment using Andisol from Tochigi Prefecture and komatsuna plant was carried out to evaluate PTC slag as liming material as well as P fertilizer. PTC slag, C slag, and dolomite were applied as liming materials and combined with super phosphate (SP). Addition of SP of 2.5 and 5.0% phosphate absorption coefficient (PAC) to PTC slag significantly improved the yield of komatsuna. This result, however, only apply for PTC slag adjusting soil pH to 6.5. Addit ono f the same dosage of SP to PTC slag adjusting soil pH to 7.5 did not give significant effect. On the other hand, addition of SP of 2.5 and 5.0% PAC to C slag or dolomite significantly improved the yield for both C slag or dolomite adjusting. the soil pH to 6.5 and 7.5. Results of the experiment also indicated that P'TC slag and C slag significantly increased soil pH; exchangeable Ca, and Mg and improved available P, B, and Mn in Andisol. The magnitudes of these effects of the two slags, however, were difference. As compared to C slag and dolomite, PTC slag increased lower exchangeable Mg but higher available P. These results suggest that for acid soil amendment, PTC slag was better than dolomite and C slag due to the fact that this material supply more P and B. Application of PTC slag as acid soil amendment will reduce the demand of P fertilizer, and even in high dosage can meet the P demand of komatsuna plant.